Minor and Toxic Element Content in Edible Mushrooms - Roushandy Asri Fardani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Minor and toxic elements in edible mushrooms are cultivated in residential areas of Mataram, West Nusa Tenggara. Minor elements are zinc (Zn), copper (Cu) and toxic elements such as lead (Pb), cadmium (Cd). Metals will be dangerous if they enter the body's metabolism in amounts that exceed the specified threshold.The purpose of this study was to determine the levels of minor elements and toxic elements in consumption mushrooms. This research was conducted to analyze minor and toxic metals using Atomic Absorption Spectrophotometer (AAS). The samples used in this study were mushrooms that are usually consumed by the public, namely, Pleurotus osteratus and Auricularia auricula-judae. The research method used is descriptive quantitative, namely to determine the levels of minor metal elements and toxic metal levels of consumption mushrooms. The results showed the highest minor levels of Zn in Pleurotus osteratus were 131.34 mg/kg and Auricularia auricula-judae mushrooms were 74.5 mg/kg. Toxic levels of Cd in Pleurotus osteratus are 0.547 mg/kg. While the levels of Cu and Pb in the analysis results are still within the maximum limit. The levels of Zn and Cd in each sample exceeded the maximum limit according to the Decree of the Directorate General of POM No. 03725/B/SK/VII/89 and the Indonesian National Standard SNI 7387:2009.